Free and Enzymatically Hydrolysed Volatile Compounds of Sweet Wines from Malvasia and Muscat Grapes (Vitis vinifera L.) Grown in Sardinia - Del Caro, A.; Fanara, C.; Genovese, A.; Moio, L.; Piga, A.; Piombino, P. (South African Journal of Enology and Viticulture, 2016)
The aroma of Muscat of Sorso-Sennori and Malvasia di Bosa wines obtained from grapes grown in Sardinia was evaluated by instrumental analysis. Gas chromatography/mass spectrometry was used to identify and quantify the content of free and bound volatile compounds. The odour activity value (OAV) was also calculated. Higher alcohols and esters were quantitatively the largest group of free volatile compounds in both wines, while terpenes were the main class of bound volatiles. A total of 52 free and 26 bound volatiles were detected. Malvasia di Bosa sweet wine had a higher content of alcohols, esters and acids in comparison to Muscat of Sorso-Sennori, which was richer in some terpenes, like nerol, geraniol and geranic acid, and also in bound volatile compounds. A total of 12 compounds were above the OAV. The main aroma-active compounds of Muscat were 3-methylbutyl acetate (banana), ethyl octanoate and hexanoate (fruity), and linalool (flowery), Malvasia wine was characterised particularly by ethyl octanoate and by 3-methylbutyl acetate.